Effects of Plant-derived Smoke, Karrikin, and Salinity Stress on Prunus armeniaca cv. Şalak seeds and seedlings: A Morphological, Biochemical, and Molecular Approach - Cüneyt Akı; Yasemin Kemeç Hürkan (Journal of Agricultural Sciences)
The effects of plant-derived smoke on seed germination and plant growth, depending on concentration and time, are widely known. However, there are very few studies demonstrating that it provides tolerance to abiotic stresses. This study comprehensively compares the effects of SW and KAR1 on seed germination and morphological, biochemical, and molecular changes observable in the examined seeds. Moreover, the study shows that it regulates the expression of some genes encoding antioxidant enzymes in apricot seedlings (Prunus armeniaca L.) exposed to salinity stress (100 mM NaCl). The highest germination rate was 1:1000 DS with 60% and 1 μM KAR1 with 72%. In terms of shoot development, root and stem length, 1:100 concentration in the DS group and 1 μM concentration in the KAR1 group gave the best results. The shoot development rates were 95.83% and 87.50% in the DS and KAR1 groups, respectively. While the root length was 137.68 and 141.92 mm in the DS and KAR1 groups, respectively, the stem length was 103.78 and 102.67 mm, respectively. The data revealed that SW (1:1000 v/v) and KAR1 (1μM) increased the expression levels of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPX) genes in the samples taken from the apricot seedlings treated with salt at hours 3, 6 and 9. This increase varies in SW and KAR1 depending on time. When the biochemical results were examined, it was seen that the application of SW and KAR1 to the seedlings under salinity stress led to a significant decrease in the thiobarbituric acid reactive substances (TBARS) content. We can assert that SW is more effective than KAR1 on TBARS content. Morphological, molecular, and biochemical results revealed enhanced germination, growth, gene expression, and TBARS content in apricot seeds and seedlings exposed to SW and KAR1. This data may be applicable to more comprehensive trials.